Pengembangan multimedia interaktif bangun ruang di MTs Negeri 2 Boalemo Provinsi Gorontalo - Bito, Nursiya; Mounte, Nur Fadlia (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The Present work was intended to develop an interactive multimedia learning materials discussing the topics of sphere fot ninth grade students of Islamics Junior High Schools. The study employed a research and development methods using a modified D model: its phases consists of three: define, design and develop. An application program called adobe flash was used to develop the learning materials. According to the results of the media and material expert from 0 to 5, the score developed materials got 4.33 (good category) and 4.28 (good category), respectively. The readability of the learning materials was measured at 3.52 on average. Further, 70% of the students responded to the interactive multimedia learning materials positively. These results signified that the develop media were appropriate to be implemented by teachers in teaching the topic of the sphere (in mathematics subject)The Present work was intended to develop an interactive multimedia learning materials discussing the topics of sphere fot ninth grade students of Islamics Junior High Schools. The study employed a research and development methods using a modified D model: its phases consists of three: define, design and develop. An application program called adobe flash was used to develop the learning materials. According to the results of the media and material expert from 0 to 5, the score developed materials got 4.33 (good category) and 4.28 (good category), respectively. The readability of the learning materials was measured at 3.52 on average. Further, 70% of the students responded to the interactive multimedia learning materials positively. These results signified that the develop media were appropriate to be implemented by teachers in teaching the topic of the sphere (in mathematics subject).